Beyond Digital Literacy: A Qualitative Inquiry into AI Readiness and Dynamic Capabilities of Micro Enterprises in North Sulawesi - Taroreh, Stefen Raymundo Agustinus; Mandalika, Wahyu; Wasilu, Irfan; Pratama, Risky; Wahyuningsih, Wahyuningsih (Yayasan Bina Lentera Insan, 2025)
The rapid spread of Generative Artificial Intelligence (GenAI) enables resource constrained businesses to leapfrog traditional development stages. However, current literature predominantly focuses on digital literacy and adoption intentions, often overlooking the strategic utilization of AI in peripheral tourism economies. This study aims to explore how micro enterprises in Bunaken, North Sulawesi, leverage AI tools to build dynamic capabilities beyond basic technical skills. Employing a qualitative descriptive design, this study investigates the lived experiences of 12 tourism based micro entrepreneurs. Data were collected through in depth semi structured interviews and digital observations. The study utilizes the Dynamic Capabilities View (DCV), specifically sensing, seizing, and transforming as the theoretical lens to analyze how participants integrate tools like ChatGPT and Gemini into their daily operations. The results reveal that AI readiness in this context is best characterized as